STRATEGI PEMERINTAH DKI JAKARTA DALAM PENATAAN DAN PEMBERDAYAAN PEDAGANG KAKI LIMA PASAR TANAH ABANG DI JAKARTA PUSAT - -, Fauziah; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER; Vol 1 No 01 (2021): Administrasi Publik 2021, 2021)
The existence of streetvendors in Tanah Abang area is considered a cause of congestion, disturbing pedestrians, and creating chaos. To overcome this problem, the DKI Jakarta Government nade one strategyor policy to organize Tanah Abang area, namely the construction of the Tanah Abang Multipurpose Crossing Bridge (JPM). Data obtained from observation, interviews , and documentation. The theory used is the theory of strategic management from Wheelen and Hunger with 4 indicators, namely environmental observation, strategy formulation, strategy implementation, evaluation and control. As well as using SWOT analysis techniques. Tanah Abang Multipurpose Crossing Bridge has not been fully maximized in overcoming the arrangement and empowerment of street vendors, low human resources, lack of awareness of traders ad the public.   Keywords : Structuring and empowering street vendors, Strategic Management, SWOT Analysis